If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(x+2)-5=22
We move all terms to the left:
9(x+2)-5-(22)=0
We add all the numbers together, and all the variables
9(x+2)-27=0
We multiply parentheses
9x+18-27=0
We add all the numbers together, and all the variables
9x-9=0
We move all terms containing x to the left, all other terms to the right
9x=9
x=9/9
x=1
| .002x+15=2 | | 4(b+5)=104 | | -2=-4+k/10 | | 7x = –56 | | -37=8+3b | | 3.46=x3.2 | | –1.4=m+–3.4 | | 2+x/18=3 | | a^2+a^2=16^2 | | 81=3*x | | -14(n+11)=42 | | 8=4b=-48 | | 13(-7-9x)+55x+63=-90 | | k5−2=2 | | -27=-5-2a | | 4(c=7) | | 9=m/3+5 | | 9=m3+5 | | 13(-7-9x)+55x+63=-93 | | p/8=7/3 | | 5.3x+1.3=7+7.3x | | -90(x+6)=-207 | | -31=-2r+7 | | s+40/9=10 | | 11z+z-2z+5z-14z=25 | | m/0.4=6 | | 91n+6+5n-31=203 | | 112+(5x-8)+(6x-12)=180 | | z/3+14=17 | | x/4-15=25 | | 13/4x22/3=x | | 12d-10d+2d+7d-10d=30 |